Colistin resistance in Parisian inpatient faecal Escherichia coli as the result of two distinct evolutionary pathways. (12th March 2019) - Bourrel, Anne Sophie; Poirel, Laurent; Royer, Guilhem; Darty, Mélanie; Vuillemin, Xavier; Kieffer, Nicolas; Clermont, Olivier; Denamur, Erick; Nordmann, Patrice; Decousser, Jean-Winoc; ,
Abstract: Background: Beyond plasmid-encoded resistance ( mcr genes) prevalence in strain collections, large epidemiological studies to estimate the human burden of colistin-resistant Escherichia coli gut carriage are lacking. Objectives: To evaluate the prevalence of colistin-resistant E. coli carriage in inpatients and decipher the molecular support of resistance and the genetic background of the strains. Methods: During a 3 month period in 2017, we prospectively screened patients in six Parisian hospitals for rectal carriage of colistin-resistant E. coli using a selective medium, a biochemical confirmatory test and MIC determination. WGS of the resistant strains and their corresponding plasmids was performed. Results: Among the 1217 screened patients, 153 colistin-resistant E. coli strains were isolated from 152 patients (12.5%). The mcr-1 gene was identified in only seven isolates (4.6%) on different plasmid scaffolds. The genetic background of these MCR-1 producers argued for an animal origin. Conversely, the remaining 146 colistin-resistant E. coli exhibited a phylogenetic distribution corresponding to human gut commensal/clinical population structure (B2 and D phylogroup predominance); 72.6% of those isolates harboured convergent mutations in the PmrA and PmrB proteins, constituting a two-component system shown to be associated with colistin resistance. Conclusions: We showed that the occurrence at a high rate of colistin resistance in human faecal E. coli is the result of two distinct evolutionary pathways, i.e. the occurrence of chromosomal mutations in an endogenous E. coli population and the rare acquisition of exogenous mcr-1 -bearing strains probably of animal origin. The involved selective pressures need to be identified in order to develop preventative strategies.